Evaluate the impacts of different straw returning rates on soil quality and field environmental sustainability of film mulching or non-mulching farmland in semiarid region - Wang, Yuhao; Ji, Yanbo; Ma, Jing; Elena, Moskvicheva; Assiya, Ansabayeva; Ding, Ruixia; Jia, Zhikuan; Siddique, Kadambot H.M.; Liu, Enke; He, Jinshang; Zhang, Weijun; Zhang, Peng (Environmental research, 2025)
Film mulching (FM) has been widely adopted in dryland agriculture to increase crop yields, but its potential long-term impacts on soil health and degradation remain a subject of debate. In contrast, straw returning (SR) has shown promising results in improving soil quality and enhancing economic returns, making it an effective measure to optimize FM practices. This study assessed the effects of varying straw return rates (0, 6, 12, and 18 t ha−1) on soil quality, ecosystem services, and economic benefits in a semiarid region, under both mulched (FM) and non-mulched conditions. Our findings indicate that FM significantly increased maize yields but also led to a depletion of soil nutrients, including organic carbon (−3.7 %) and total nitrogen (−5.8 %), while increasing CO2 emissions (9.9 %). In contrast, SR increased soil nitrogen (11.9 %), organic carbon (6.6 %), and improved both particulate organic carbon (19.2 %) and dissolved organic carbon (37.4 %). Moreover, both FM and SR improved soil enzyme activity (catalase, cellulase, and urease) and enhanced the stability of soil aggregate structure, particularly through the coupling effects of FM and SR. However, this coupling effect also resulted in increased greenhouse gas emissions (CO2: 15.0 %; N2O: 8.1 %), although it reduced the carbon footprint (−22.0 %) and improved economic returns (10,074 yuan ha−1). From the perspective of both environmental sustainability and stable economic returns, we recommend the return of all straw (12 t ha−1) to dryland mulching cropland. To further enhance soil quality, we suggest increasing the amount of straw (18 t ha−1). •Straw returning can alleviate soil environment degradation caused by film mulching.•Biological property is an important factor to improve soil quality index of straw.•From the perspective of environment pollution and economic benefit, full amount of straw returning is suitable.•Increasing the amount of straw returning promotes soil quality and resource recycling.